Hypospadias Repair Using Transverse Preputial Island Flap (Modified Asopa Procedure) - Patil, Abhijeet; Sharma, Amit; Mane, Narsing; Parab, Sandesh; Andankar, Mukund; Pathak, Hemant (Journal of Pediatric Nephrology, 2019)
Introduction: The modified Asopa’s procedure for repair of hypospadias is well established and suited for patient characteristics for which Snodgrass urethroplasty cannot be done. We describe our experience with this procedure in 30 patients managed with this procedure highlighting the factors affecting outcome in this repair. Materials and Methods: Data of 30 patients (age range 2.5-15 years) who underwent hypospadias repair in a tertiary care teaching institution from 2012 to 2015 with modified Asopa procedure (Hodgson XX technique) utilizing Transverse Preputial Island Flap by a single surgeon were reviewed and retrospectively analyzed according to age of patients, site of meatus, presence or absence or chordee, glans configuration and complications - fistula, glans dehiscence, meatal stenosis. These complications were further analyzed with respect to the various patient characteristics and GMS (Glans, Meatus and Shaft) score. Results: The mean age of presentation was 5.5 years and mean follow-up period was 22 months. The mean total GMS score was 8.5; range being 11 to 5. In total, only six patients had complications (20%). The patients with low GMS score (7 or less) had no complications. The complication rate was more in proximal hypospadias repair (n= 5/24) when compared with distal hypospadias (n=1/6). There were more complications in patients with chordee (n=4/6) and those with conical glans (n=4/6). Conclusion: Location of the meatus, presence/absence of chordee and glans configuration affect outcome in patients undergoing modified Asopa’s procedure for hypospadias repair. Keywords: hypospadias; Asopa’s procedure; Child; Complications; Outcome.